The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d2ay01989b
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic covalent organic frameworks for rapid solid-phase extraction of phthalate esters and bisphenol A in beverage samples

Abstract: Phthalate esters (PAEs) and bisphenol A (BPA) are endocrine-disrupting chemicals (EDCs), which are widely used in the production of food plastic packaging and easily migrate to food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…4–6 In addition, BPA is an important synthetic raw material in the chemical industry and in the production of consumer products, including food containers and packaging materials, where it is commonly utilized. 7–9 Studies have shown that BPA can leach from drinking water bottles and food cans and accumulate in various tissues when it enters the body with food. 10–12 It has been shown that the availability of binding enzymes is low in infants and young children, which is expected to lead to the accumulation of free BPA levels.…”
Section: Introductionmentioning
confidence: 99%
“…4–6 In addition, BPA is an important synthetic raw material in the chemical industry and in the production of consumer products, including food containers and packaging materials, where it is commonly utilized. 7–9 Studies have shown that BPA can leach from drinking water bottles and food cans and accumulate in various tissues when it enters the body with food. 10–12 It has been shown that the availability of binding enzymes is low in infants and young children, which is expected to lead to the accumulation of free BPA levels.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the analysis of PAE is mainly carried out by chromatographic methods, for example, high-performance liquid chromatography (HPLC) [29], ultra HPLS using a sustainable natural deep eutectic solvent-based analytical methodology [30] or gas chromatography-mass spectrometry (GC-MS) [8,9,[31][32][33][34][35][36]. These analytical methods allow accurate and sensitive quantitative analysis; however, they require expensive instrumentation, highly skilled personnel and complex sample processing that cannot meet the requirements for rapid detection of toxicants outside the laboratory.…”
Section: Introductionmentioning
confidence: 99%